Breaking the two-party doom loop eaudiobook The case for multiparty democracy in america. - Drutman, Lee (Kalorama, 2020)
American democracy is at an impasse. After years of zero-sum partisan trench warfare, our political institutions are deteriorating. Our norms are collapsing. Democrats and Republicans no longer merely argue; they cut off contact with each other. In short, the two-party system is breaking our democracy, and driving us all crazy. Deftly weaving together history, democratic theory, and cutting-edge political science research, Lee Drutman tells the story of how American politics became so toxic, why the country is trapped in a doom loop of escalating two-party warfare, and why it is destroying the shared sense of fairness and legitimacy on which democracy depends. He argues that the only way out is to have more partisanship-more parties, to short-circuit the zero-sum nature of binary partisan conflict. Breaking the Two-Party Doom Loop makes a compelling case for large scale electoral reform-importantly, reform not requiring a constitutional amendment-that would give America more parties, making American democracy more representative, more responsive, and ultimately more stable.